Analisis kinerja pengembalian saham perbankan di Indonesia - Mea, Florensi Ekaristi; Garus, Olivia Ribka (Yayasan Widyantara Nawasena Raharja, 2023)
In early March 2023, banking liquidation in the US will become an important issue in world capital markets. This study aims to analyze risk-return performance throughout the issue period. This study uses 45 issuers registered in the banking sector. The observation period was carried out from 7 February 2023 to 6 April 2023 with cut-off points of 7 March 2023 and 8 March 2023. The findings of this study show that the performance of stock returns in the period before the liquidation issue tended to be better than in the period after the issue. In the period following the issue of banking liquidation in the US, average stock returns were lower but accompanied by high market risk. This indicates that an increase in risk tends to be accompanied by a decrease in stock returns.